Seafood Safety. (Online access: NCBI NCBI Bookshelf., 1991)
"Can Americans continue to add more seafood to their diets without fear of illness or even death? Seafood-caused health problems are not widespread, but consumers are at risk from seafood-borne microbes and toxins--with consequences that can range from mild enteritis to fatal illness. At a time when legislators and consumer groups are seeking a sound regulatory approach, Seafood Safety presents a comprehensive set of practical recommendations for ensuring the safety of the seafood supply. This volume presents the first-ever overview of the field, covering seafood consumption patterns, where and how seafood contamination occurs, and the effectiveness of regulation. A wealth of technical information is presented on the sources of contamination--microbes, natural toxins, and chemical pollutants--and their effects on human health. The volume evaluates methods used for risk assessment and inspection sampling."